Sustainable Magnetic Biocomposites Palm Oil Empty Fruit Bunch/Sago Dregs-Based with High Active Amine as Green Materials - Naufal, Allam; Irawan, Chairul; Juwita, Rinna; Nata, Iryanti (Jurnal Bahan Alam Terbarukan, 2024)
Palm oil empty fruit bunches (POEFB) and sago dregs (SD) are agricultural wastes that contain cellulose fibers. The one of utilization is used as raw materials for magnetic biocomposites. The objectives of this research are to determine the optimal composition of POEFB-SD fibers for the formation of amine magnetic biocomposite. The resulting biocomposite is characterized based on morphological, amine content, elemental content, crystalline structure, and functional groups. First, POEFB and SD)fibers were dried and ground to approximately 60 mesh. These fibers then underwent delignification at 80 °C for 2 h using a 1% w/v NaOH solution. A one-step solvothermal process followed, wherein different ratios of delignified POEFB and SD fibers (1:0; 1:1; 1:2; and 1:3) were added to a mixture containing ethylene glycol, FeCl3·6H2O, and 1.6-hexanediamine, and heated to 200 °C for 6 h. The resulting magnetic biocomposites contain Fe and amine at about 98.26% and 3.83 mmol.g, respectively. The magnetite was confirmed by X-Ray diffraction (XRD) through characteristic peaks at 36°, 43°, and 57°. Furthermore, Fourier-Transform Infrared Spectroscopy (FT-IR) revealed N–H bending vibrations and Fe-O bonds in the biocomposites at 1620 cm−1 and 585 cm−1, respectively. The arrangement of the matrix, iron, and amine groups on the biocomposites' is promising candidates as good adsorbents for advanced biocomposites and green materials.